PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP KINERJA PENGELOLA ANGGARAN DENGAN SPIP SEBAGAI VARIABEL MODERASI - Saputra, Rifki Yus; Netty Herawaty; Eko Prasetyo (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
The phenomenon of delays in the disbursement of Employee Income Supplements (TPP) for up to six months and a decrease in budget realization in Batang Hari Regency reflects the weak implementation of good governance principles, particularly accountability, transparency, and internal control. This study aims to analyze the influence of accountability and transparency on the performance of budget managers with the Government Internal Control System (SPIP) as a moderator. The method used is a quantitative approach and uses a questionnaire as a data source. The study population includes 28 agencies, with a purposive sample of 32 TPP management employees in six main agencies. The data analysis process uses the SmartPLS 4 tool with the Structural Equation Modeling (SEM) principle with Partial Least Square (PLS). This study shows that accountability has no effect on the performance of budget managers, while transparency has a significant positive effect. SPIP has no direct effect on performance and does not moderate the relationship between accountability and performance. However, SPIP actually weakens the effect of transparency on performance, indicating that SPIP implementation has not been optimal. These findings confirm that transparency is an important factor in improving the performance of budget managers, while ineffective SPIP has the potential to reduce transparency. Keywords: : Accountability, Transparency, Spip, Budget Performance, Good Governance